DEVELOPMENT OF THE AEROSPACE INDUSTRY OF UKRAINE - Жмур, Наталія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Goal: identify the preconditions and prospects of development of the aerospace industry of Ukraine. Research methods: the general scientific and special methods were used in the work. Results: development of the aerospace industry was investigated and analyzed. Assessing the level of funding and identifying possible ways to improve approaches to ensuring the efficient financing of enterprises in the aerospace industry in Ukraine. The increase in demand for civilian aircraft, which corresponds to some brands of Ukrainian airplanes, and the reduction of the fleet of «An» aircraft in connection with the decommissioning of predominantly outdated aircraft, is accompanied by a reduction in domestic airplanes production starting in 2007. However, for the change of such a disadvantageous situation for Ukraine, we have a research-and-production potential, the implementation of which is paid attention by the state, as well as foreign partners. The state of the space industry is in the best position, but the results of the industry should be more appropriate for the needs of the domestic market. In general, one of the effective ways of overcoming the economic crisis in Ukraine is the restructuring of industry on the basis of intensive development of production of high-tech products, the list of which includes products of aircraft building and space industries. Under market conditions, it creates objective prerequisites for increasing the efficiency of social production on the basis of resource conservation and environmental friendliness. The increase in the own production of high-tech products today depends on a large extent on the wider use of state-of-the-art technology, modern forms of production management organization, and the introduction of an effective market management mechanism. Discussion: prospects of development of the aviation and space industry, improving of financing of the industry.